Valoración del acceso del microcrédito a través de la banca tradicional para el desarrollo y crecimiento de los microempresarios en el barrio Santa Anita al sur de Quito - Smith Borja, Nastia Paulina (2015)
The study is a compressive analysis of the impact that microcredit has a very important sector of our economy. It is the microenterprise sector, due to the rise of products that offer market and that have been so popular to use them by this sector, there has been a historical survey of the evolution that has taken the microcredit from its origins and it has been developing and taking shape in our economy. I consolidated information from many sources, which have contributed significantly to the development of the information, and used tools necessary to obtain it. The job basically is divided into chapters, which focus on issues such as: thesis plan in the first instance; dealing the problematic, intent and purpose of the study, then the global historical analysis, implementation in our country; how and why it has become a very common practice in the sector and an analysis of the real situation of microcredit. It was taken as basis of the study to the neighborhood of Santa Anita in southern Quito by considering a sector where the influx of entrepreneurs is notorious and collected; through surveys, most information possible to identify the main objective of this project. It should be noted, that it was difficult to access information because people were reluctant industry to deliver the same as they had a misconception use your financial information.